The Effect of Halal Certificate towards Chicken Meat Import between Brazil and Indonesia according to Rule of GATT – WTO - Hamzah, Hamzah; Ayodahya, Devika Tryza; Haque, MD. Sharifu (Universitas Islam Negeri Raden Intan Lampung, 2019)
Trade activity is one of the drivers of development in a country in order to obtain national development. In the current era of globalization, trade activities opened among the countries have developed quite rapidly. Indonesia has acquired a spinning wheel in international trade activities. Indonesia is actively involved in several negotiations concerning international trade and actively supports the national development. By becoming a member of the World Trade Organization, Indonesia has carried out important export activities to all parts of the world. Indonesia itself has special rules regarding important goods, specifically about food ingredients. Indonesia stops importing chicken because of the absence of halal labeling on these food ingredients. Indonesia is a country which most of its citizens are Muslim. Food which is consumed for Indonesia Muslim people is not only about safe and healthy but also about halal . Due to this rule, Brazil suffered a quite big loss and filled a lawsuit to WTO. The purpose of this study was to analyze the Indonesian national law regarding halal certification and how to resolve the dispute between Brazil and Indonesia on the issue of importing chicken meat.Keywords: Consumer Protection, Halal Certificate, WTO.